(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
This article deals with improving the skills of wrestlers, a high level of technical training, the qualities of fatigue, the impact of fatigue on the functional state of the body, the dependence of physical activity on movement games.